Prevalence of abnormal seminal fluid and associated factors among patients attending fertility clinics in Osogbo: a cross-sectional study - Kehinde Awodele; Sunday Charles Adeyemo; Eniola Dorcas Olabode; Adeniyi Olanipekun Fasanu; Lanre Olaitan; Akintunde Rasaq Akindele; Funso Abidemi Olagunju; Adeola Dorcas Aderinwale (Journal of Men's Health)
Background: Infertility is a global health issue affecting millions of couples worldwide. In Nigeria, the prevalence of infertility is particularly high, underscoring the need for a better understanding of the factors contributing to male infertility, with Seminal Fluid Analysis (SFA) being a critical diagnostic tool. This study aimed to assess the prevalence of abnormal seminal fluid and its associated factors among patients attending fertility clinics in Osogbo, Nigeria. Methods: A descriptive cross-sectional study design was used among male patients attending fertility centers in Osogbo, Osun State. Fisher’s formula (n = z2pq/d2) was used to determine the sample size, and 305 respondents were selected using a multistage sampling technique. A pre-tested questionnaire was used to collect data from respondents, and those who consented to participate underwent SFA. Data were analyzed using IBM Statistical Product for Service Solution (SPSS) version 27. Descriptive statistics were performed for all variables, while bivariate and multivariate analyses were conducted at a significance level of p < 0.05. Results: The majority of the respondents, 257 (84.3%), had at least one abnormality in their seminal fluid. Multiple regression analysis revealed that habitual drunkards were approximately five times more likely to have at least one abnormality in their seminal fluid (Odd’s ratio (OR): 4.990, p: 0.004, Confidence Interval (CI): 1.688–14.749), while smokers were three times more likely to have at least one abnormality in their seminal fluid (p = 0.005, OR = 3.300 and CI = 1.396–4.273). Additionally, respondents with a history of sexually transmitted infections were 3.5 times more likely to have at least one abnormality in their seminal fluid (p = 0.039, OR = 3.595 and CI = 1.072–14.146). Conclusions: This study observed a high prevalence of abnormal seminal fluid, which was significantly associated with lifestyle habits such as smoking and alcohol consumption, as well as a history of sexually transmitted infection.